BEHAVIOUR OF SURFACTANTS AS ADDITIVES IN WATER-BASED DRILLING FLUID - YUNITA, PUTRI (2016)
During drilling process, very important to select the suitability of drilling fluid used. Suitability of drilling fluid selection is important to reserve the maximum drilling performance. To complete the missions that have maximum wellbore performance, there are two problems have to avoid; lost circulation and shale instability. The common case in the drilled infill wells is high-formation damage. Generally, one of popular drilling fluids was oil base mud (OBM).